Chasing literacy: reading and writing in an age of acceleration - Keller, Daniel, author; Utah State University Press, publisher (Colorado State University. Libraries, 2013)
Arguing that composition should renew its interest in reading pedagogy and research, Chasing Literacy offers writing instructors and literacy scholars a framework for understanding and responding to the challenges posed by the proliferation of interactive and multimodal communication technologies in the twenty-first century. Employing case-study research of student reading practices, Keller explores reading-writing connections in new media contexts. He identifies a culture of acceleration--a gathering of social, educational, economic, and technological forces that reinforce the values of speed, efficiency, and change--and challenges educators to balance new faster literacies with traditional "slower" literacies. In addition, Keller details four significant features of contemporary literacy that emerged from his research: accumulation and curricular choices; literacy perceptions; speeds of rhetoric; and speeds of reading. Chasing Literacy outlines a new reading pedagogy that will help students gain versatile, dexterous approaches to both reading and writing and makes a significant contribution to this emerging area of interest in composition theory and practice.--Provided by publisher.
Locating reading in composition studies -- Perceptions of literacy -- Reading in a culture of acceleration -- Directing attention: multitasking, foraging, oscillating -- Reading-writing connections.
Keywords: Reading; Information technology; Literacy